A new species of Lophogyne s.l. (Podostemaceae) from the Amazonian savanna of Amapá, Brazil - Bove, Claudia P.; Philbrick, C. Thomas; Lourenço, Arthur R. (Phytotaxa, 2020)
A new species of Lophogyne from a Brazilian Amazon savanna is described and illustrated. It is morphologically similar to the former Jenmaniella species, due to the presence of stems that arise from prostrate roots attached to the substratum, a gynophore at anthesis, and three prominent non-suture ribs per valve in the fruit, currently merged in Lophogyne s.l.. Lophogyne wilsonii can be distinguished from all others species of  Lophogyne s.l. by the apical region of the roots unattached from the substratum. The conservation status is discussed and an identification key is presented.